Outcomes of Exercise Interventions in Patients With Advanced Liver Disease: A Systematic Review of Randomized Clinical Trials. (12th October 2022) - Jamali, Taher; Raasikh, Taaj; Bustamante, Gabriel; Sisson, Amy; Tandon, Puneeta; Duarte-Rojo, Andres; Hernaez, Ruben
Abstract : INTRODUCTION: Frailty and sarcopenia are common complications of advanced liver disease. Owing to associated morbidity/mortality, there have been targeted efforts to prevent and/or improve both by enrolling these patients in focused exercise programs. This review systematically analyzes the data of randomized clinical trials (RCTs) on anthropometric, physical fitness, quality-of-life, and safety outcomes of exercise interventions in patients with advanced liver disease. METHODS: Two authors independently searched trials on PubMed and EMBASE from inception up to November 18, 2021. A third independent arbitrator adjudicated all disagreements. We qualitatively summarized these outcomes as follows: (i) muscular fitness (maximal inspiratory/expiratory pressures, muscle size, muscle strength, and bioimpedance testing), (ii) cardiorespiratory fitness (cardiopulmonary exercise testing and 6-minute walk distance), (iii) quality of life, and (iv) others (safety or frailty indices). RESULTS: There were 11 RCTs (4 home-based interventions) with 358 participants. Interventions ranged from 8 to 14 weeks and included cycling, walking, resistance exercises, balance and coordination training, and respiratory exercises. All described outcomes compared preintervention with postintervention measurements. Nine studies showed statistically significant improvements in at least 1 physical fitness variable. Ten studies showed statistically significant improvements in at least 1 muscular fitness variable. Six studies showed statistically significant improvements in at least 1 quality-of-life variable. Attrition rates ranged from 5% to 36%, and adherence rates ranged very widely from 14% to 100%. Only 1 study reported frailty indices. Notably, no complications of portal hypertension were seen in intervention groups in the 9 studies that reported these data. DISCUSSION: A review of 11 RCTs with 358 participants with advanced liver disease demonstrates that exercise interventions can have favorable outcomes on muscular/cardiorespiratory fitness and quality of life. Although attrition and adherence varied, these interventions seem to be safe in patients with cirrhosis and are well tolerated.